Analysis of Contact Dermatitis Incidence Factors in Fishermen in The Working Area of Wapunto Health Center - L., Titi Saparina; Sya’ban, Abdul Rahim; Kasih, Ridia Utami; Ali, Leniarti; Solihin, Solihin; Firmansyah, Firmansyah (Poltekkes Kemenkes Palu, 2023)
The prevalence of contact dermatitis in the Working Area of Wapunto Public Health Center, increases yearly, that is, in 2018 was 22.3% per 1000 population, in 2019, was 29.4% in 2020, was 35.2%. The purpose of this study was to determine the factors related to contact dermatitis disease in fishermen in the Working Area of Wapunto Public Health Center, Muna Regency. The type of study was observational quantitative with a cross-sectional study design. The total population in this study were 255 families, while the sample was 72 respondents using cluster random sampling. Data analysis using chi-square test. The results of the study showed that there was a relationship between contact time with value X2count > X2table, namely 19,412 > 3,481, personal hygiene with value X2count > X2table namely 26,331 > 3,481, history of allergies with value X2count > X2table, namely 11,250 > 3,481, use of PPE with value X2count > X2table namely 31,065 > 3,481 with contact dermatitis disease in fishermen in the Working Area of Wapunto Public Health Center, Muna Regency. In conclusion, there is a relationship between contact time, personal hygiene, history of allergies, and PPE use. Therefore, fishermen should reduce the risk or prevent the incidence of contact dermatitis by further improving personal hygiene, such as washing hands and feet using soap, changing work clothes and using clean and not humid PPE.